Staging musicals : an essential guide - White, Matthewan (Methuen drama, 2019)
Ever dreamt of putting on a musical from scratch? Or perhaps you already have, but some extra guidance would be welcome. Look no further: this book will give you all the information you need to successfully stage a musical.